PENGARUH KEPEMIMPINAN, KOMPETENSI, DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU PADA SEKOLAH MENENGAH PERTAMA NEGERI 3 SELEMADEG TIMUR - Putu Kristina Putri; Ni Putu Ayu Sintya Saraswati; Ary Wira Andika (VALUES, 2024)
The aim of this research is to examine and analyze the influence of leadership, competence and emotional intelligence on teacher performance at East Selemadeg 3 State Junior High School. The sample in this research were all 32 teachers at East Selemadeg 3 State Junior High School. The data analysis technique uses multiple linear regression analysis to answer the problem formulation with the help of the SPSS Version 25 For Windows program. The results of testing the hypothesis show that: 1) Leadership (X1) has a positive effect on teacher performance, 2) Competency (X2) has a positive effect on teacher performance, and 3) Emotional Intelligence (X3) has a positive effect on teacher performance.